Gamification 2015
DOI: 10.4018/978-1-4666-8200-9.ch076
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Facebook as a Pedagogical Platform for Developing Investigative Journalism Skills

Abstract: This chapter evaluates the extent to which Facebook could be used as a training and learning tool for investigative journalism students. This study is based on the deployment of Facebook as a pedagogical tool for an “Investigative Journalism” unit at Swinburne University of Technology, Melbourne, Australia. This chapter, accordingly, outlines the challenges, issues, and benefits of using Social Networking Services (SNS) as pedagogical tools for the training of future investigative journalists, which could in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…This study's findings resonated well with other recent research demonstrating that students overall see blended learning positively (Khine & Lourdusamy, 2003;Owston et al, 2013), crediting it with flexibility and accessibility among other study-friendly features. Our findings concerned with social media are also reflective of prior research (Aayeshah & Bebawi, 2014) which showed that students are likely to utilize social media for peer networking rather than for learning purposes. The most interesting findings, however, emerge in regards to students' use of educational technologies.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study's findings resonated well with other recent research demonstrating that students overall see blended learning positively (Khine & Lourdusamy, 2003;Owston et al, 2013), crediting it with flexibility and accessibility among other study-friendly features. Our findings concerned with social media are also reflective of prior research (Aayeshah & Bebawi, 2014) which showed that students are likely to utilize social media for peer networking rather than for learning purposes. The most interesting findings, however, emerge in regards to students' use of educational technologies.…”
Section: Discussionsupporting
confidence: 82%
“…However, the 'cons' of social media use for teaching and learning include excessive informational convergence and proximity to entertainment content, meaning students can be distracted when accessing social media for learning and waste valuable study time on entertainment and social networking (Tiryakioglu & Erzurum, 2011). An ethical implication of using social media for learning is that students are likely already using it for private purposes and may not wish to combine their private and public spaces, where related issues of privacy and security arise (Aayeshah & Bebawi, 2014;Çoklar, 2012). Finally, the issues of assessment of performance and grading of students' work performed via social media platforms present several challenges (Çoklar, 2012).…”
Section: Social Media As a Learning Toolmentioning
confidence: 99%
“…Mark Zuckerberg and the other creators of Facebook intended Facebook for university use: it was designed as a tool for Harvard University students to establish virtual connections (Jenkins 2013). Regardless of the original social intentions for Facebook, it now has substantial potential as a pedagogical tool (Aayeshah & Bebawi, 2014;Best et al, 2014;Dogoriti & Pange, 2014;Jaffer, 2014;Joosten, 2012;McEwan, 2012;Saykili & Kumtepe, 2014). In particular, the features Facebook Pages and Facebook Groups have been used for academic purposes (see section below titled Case Studies and Best Practices).…”
Section: Attitudes Surrounding the Decision To Forego Facebookmentioning
confidence: 99%
“…The first possible reason is because Facebook operates on the exchange of personal information, so using this technology for teaching and learning can be challenging for some faculty (Aayeshah & Bebawi, 2014;Auld & Henderson, 2014;Howard, 2013;McEwan, 2012). In the U.S., there are concerns about the Family Educational Rights and Act (FERPA).…”
Section: Attitudes Surrounding the Decision To Forego Facebookmentioning
confidence: 99%
See 1 more Smart Citation